Evaluation of The Role and Position of Dispute Resolution Councils In Iran's Criminal Policy In Comparison with Similar Institutions In The French Judiciary - Hassan Vahedi; Abdolvahid Zahedi; Firooz Mahmoudi Janaki (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
The Dispute Resolution Council was established as a public institution in the last few decades to reduce the number of cases sent to the judiciary in Iran and strengthen public participation and increase the role of the people in criminal justice policy. Although the activities of this institution in recent years have led to a decrease in the number of cases sent to judicial institutions, but its public aspect was not fulfilled as intended. In addition, the law of this council has many contradictions with the constitution with limitations and problems in the legal and structural field that have affected its functions. However, the role of the people is significant in similar institutions in the legal system of the Common Law and France, while strengthening the participatory aspect. This issue has been an effective measure in strengthening participatory criminal policy in these countries. The purpose of this research was to investigate the criminal policy of the Dispute Resolution Council and similar institutions in France.Keywords: Dispute Resolution Council, French Law, Iranian Criminal Justice Policy Evaluasi Peran dan Kedudukan Dewan Penyelesaian Sengketa Dalam Kebijakan Pidana Iran Dibandingkan dengan Institusi Serupa di Peradilan Prancis AbstrakDewan Penyelesaian Sengketa didirikan sebagai lembaga publik dalam beberapa dekade terakhir untuk mengurangi jumlah kasus yang dikirim ke peradilan di Iran dan memperkuat partisipasi publik dan meningkatkan peran masyarakat dalam kebijakan peradilan pidana. Meskipun kegiatan lembaga ini dalam beberapa tahun terakhir telah menyebabkan penurunan jumlah kasus yang dikirim ke lembaga peradilan, tetapi aspek publiknya tidak terpenuhi sebagaimana dimaksud. Selain itu, undang-undang dewan ini memiliki banyak kontradiksi dengan konstitusi dengan keterbatasan dan masalah di bidang hukum dan struktural yang mempengaruhi fungsinya. Namun, peran masyarakat cukup signifikan dalam lembaga sejenis dalam sistem hukum Common Law dan Perancis, sekaligus memperkuat aspek partisipatif. Isu ini telah menjadi langkah yang efektif dalam memperkuat kebijakan kriminal partisipatif di negara-negara tersebut. Tujuan dari penelitian ini adalah untuk mengetahui kebijakan kriminal dari Dispute Resolution Council dan lembaga sejenis di Perancis.Kata Kunci: Dewan Penyelesaian Sengketa, Hukum Prancis, Kebijakan Peradilan Pidana Iran Оценка роли и позиции советов по решению спорных вопросов В уголовной политике ирана по сравнению с аналогичными учреждениями во французской судебной системе АннотацияСовет по решению спорных вопросов был создан как государственное учреждение в последние десятилетия для сокращения количества дел, передаваемых в судебные органы в Иране, и расширения участия общественности и повышения роли общественности в политике уголовного правосудия. Хотя деятельность этого учреждения в последние годы привела к уменьшению количества дел, направляемых в судебные органы, общественный аспект не выполняется должным образом. Кроме того, закон этого совета имеет много противоречий с конституцией с ограничениями и проблемами в правовой и структурной областях, которые влияют на его функционирование. Тем не менее, роль сообщества весьма значительна в аналогичных учреждениях в системе общего права и правовой системы Франции, а также в усилении аспекта участия. Этот вопрос стал эффективным шагом в укреплении совместной уголовной политики в этих странах. Целью данного исследования является определение уголовной политики Совета по разрешению спорных вопросов и аналогичных учреждений во Франции.Ключевые Слова: Совет по решению спорных вопросов, Французское право, политика в области уголовного правосудия в Иране